Aligning knowledge strategy and competitive strategy in small firms - Bagnoli, Carlo; Giachetti, Claudio (Journal of Business Economics and Management, 2014)
Despite the claim of more and more scholars that there is a need to align knowledge strategies with competitive strategies, little research allows for more precise conceptualizations concerning this problem of inter-level strategic fit, and few have attempted an empirical investigation. This is especially true in the specific context of small firms (SFs), despite the fact, that their knowledge-based resources are more important than their property-based resources. This study aims to investigate, through a quali-quantitative analysis carried out on a sample of SFs in northeast Italy, the alignment between knowledge strategies and competitive strategies. We have identified two types of competitive strategies pursued by SFs, i.e. human resource-based (HR-based) and product and customer service quality-based (PCSQ-based). We have also identified two types of internal knowledge strategy, i.e. exploitation strategy of internal knowledge, and exploration strategy of internal knowledge, as well as two types of external knowledge strategy, i.e. exploitation strategy of external knowledge, and exploration strategy of external knowledge. Our findings reveal that SFs pursuing HR-based competitive strategies tend to adopt exploitation strategies of both internal and external knowledge, while firms pursuing PCSQ-based competitive strategies tend to adopt exploration strategies of both internal and external knowledge. First published online: 02 Jan 2014